2010
DOI: 10.3390/ijerph7052274
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Measurement in Economic Evaluations of Public Health Interventions: a Role for the Capability Approach?

Abstract: Public health interventions have received increased attention from policy makers, and there has been a corresponding increase in the number of economic evaluations within the domain of public health. However, methods to evaluate public health interventions are less well established than those for medical interventions. Focusing on health as an outcome measure is likely to underestimate the impact of many public health interventions. This paper provides a review of outcome measures in public health; and describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
118
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(126 citation statements)
references
References 88 publications
(121 reference statements)
0
118
0
8
Order By: Relevance
“…It is designed to measure a core set of domains believed to impact on quality of life and linked to health. However, with this focus on certain aspects of health, the EQ-5D may not adequately reflect the impact of all health care interventions [10], such as for hearing or vision disorders [11], and severe mental health problems [12], and particularly of those resulting in broader personal and interpersonal wellbeing benefits, such as public health and social care interventions [13][14][15][16][17][18][19]. An alternative framework for measuring treatment benefits is with the ICEpop CAPability (ICECAP) measures, underpinned by Amartya Sen's capability approach [20].…”
Section: Introductionmentioning
confidence: 99%
“…It is designed to measure a core set of domains believed to impact on quality of life and linked to health. However, with this focus on certain aspects of health, the EQ-5D may not adequately reflect the impact of all health care interventions [10], such as for hearing or vision disorders [11], and severe mental health problems [12], and particularly of those resulting in broader personal and interpersonal wellbeing benefits, such as public health and social care interventions [13][14][15][16][17][18][19]. An alternative framework for measuring treatment benefits is with the ICEpop CAPability (ICECAP) measures, underpinned by Amartya Sen's capability approach [20].…”
Section: Introductionmentioning
confidence: 99%
“…Sen's capability approach has been argued to provide many 646 benefits particularly when seeking to evaluate the cost effectiveness of such interventions and 647 programmes Lorgelly et al 2010). It offers a much richer set of dimensions for evaluation, 648 thereby potentially capturing all relevant outcomes, rather than focusing solely on health 649 status (as is the current approach in health economics) (Coast, Smith & Lorgelly 2008a).…”
Section: Discussion 643mentioning
confidence: 99%
“…This project operationalised the capability approach to 22 produce an instrument to measure the effectiveness (and cost effectiveness) of public health 23 interventions; the resulting OCAP-18 appears to be responsive and measure something 24 supplementary to health and wellbeing, thus offers a promising addition to the current suite of 25 outcome measures that are available. Sen's Capability Approach (Sen 1985;1993) would appear to provide a possible solution to 77 the limitations of QALYs, as it expands the evaluative space (so it can include non-health 78 outcomes like empowerment, participation, housing, and crime) to consider whether a 79 programme/policy/intervention enhances an individual's capability (Lorgelly et al 2010). 80…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are known as 'inter-sectoral costs and benefits' (ICBs) [1][2][3]. Drost et al identified more than 70 ICBs of health-care interventions, which were classified into five categories.…”
Section: Introductionmentioning
confidence: 99%